The Aurora borealis harmony as structural design in Eduard Tubin’s ‘Northern Lights’ Piano Sonata No. 2 - Jurkowski, Edward (Les Cahiers de la Société québécoise de recherche en musique, 2013)
The Estonian Eduard Tubin’s (1905-1982) second piano sonata, subtitled the “Northern Lights Sonata,” represents a significant turning point for the composer. Written between February and October in 1950, the sonata contains attributes that become hallmarks of Tubin’s mature style—namely, a highly concentrated compositional structure, an enriched, tonally ambiguous harmonic design, and the use of cyclically repeating theme groups. The subtitle of the composition comes from Tubin himself. Specifically, he noted that the work’s opening eight-note harmony represents the programmatic depiction of the whirling flashes from the northern lights he witnessed in Stockholm during 1949. In this article, I trace the various transformations of the Aurora borealis harmony in the second piano sonata and identify its role as a vital structural element of the composition. Following a descriptive assessment of the work’s three movements, I end by identifying some fascinating relationships between the piano sonata and other works by Tubin from this time period.